Experimental and theoretical study on Fe(VI) oxidative degradation of dichlorophen in water: Kinetics and reaction mechanisms. (1st August 2022) - Fei, Yi; Liu, Zhuangzhuang; Meng, Liang; Liu, Guoqiang; Kong, Deyang; Pan, Xiaoxue; Zhu, Feng; Lu, Junhe; Chen, Jing
Abstract: Dichlorophenol (DCP), a commonly used fungicide and insecticide, is widely found in waters and wastewaters. Herein, the degradation of DCP by Ferrate (Fe(VI)) in different matrices was comprehensively investigated. In pure water, a complete removal of DCP was achieved in 300 s at [Fe(VI)]:[DCP] molar ratio of 2:1. The presence of HA (10 mg L −1 ) inhibited DCP degradation to a certain extent. A total of twenty degradation products were identified by HPLC/MS analysis. Based on these products, reaction pathways including the cleavage of C–C bridge bond, hydroxylation, and radical coupling were proposed. These reaction mechanisms were further rationalized by theoretical calculations. The analyses of Wiberg bond orders and transition state indicated that C7 –C8 bond was the most vulnerable site for cleavage, and C12 site was the most likely site for hydroxyl addition. Mulliken atomic spin densities distribution suggested that self-coupling products was easily generated via C–O–C coupling ways. Finally, the feasibility of applying Fe(VI) to degrade DCP (20 μM) in a municipal wastewater effluent and a lake water was evaluated and verified. The findings in this study are of relevance in designing Fe(VI)-based treatment strategy for chlorine-containing persistent pesticides. Graphical abstract: Image 1 Highlights: Dichlorophenol (DCP) was efficiently removed in Fe(VI) oxidation process. A total of 20 transformation intermediates were identified. Reaction pathways of DCP mainly involve cleavage of C–C bridge bond, hydroxyl addition, and radical coupling.